Enhalus acoroides responses to experimental shoot density reductions in H aad C hao M ai N ational P ark, T rang P rovince, T hailand - Ekkalak Rattanachot; Frederick T. Short; Anchana Prathep (Marine Ecology, 2016)
The effect of self‐shading and competition for light in the seagrass Enhalus acoroides were investigated with a density reduction experiment in Haad Chao Mai National Park, Trang Province, Thailand. The study was carried out in a monospecific meadow with a natural density of 141.0 ± 8.7 shoots·m −2 . The intent was to determine the response of E. acoroides beds to loss of shoots and thinning, which often occur during typhoons and severe storm activity. Permanent quadrats were manipulated by clipping the seagrass shoots to 140, 72, 36 and 16 shoots·m −2 , to yield natural, 50%, 25% and 10% densities, respectively. Reducing shoot density in E. acoroides increased underwater light intensity below the canopy, generating increased leaf surface area and shoot weight. Seagrass leaf width, growth rate, and number of leaves per shoot also increased with greater light. The extent of flowering varied among treatments with no consistent trend. Our results demonstrate that increasing the available light to E. acoroides produces an increasing leaf size response as self‐shading in the bed is reduced.